Education and Curriculum Reform: The Impact They Have On Learning - Sharon Campbell-Phillips (BIRCU, 2020)
Globally, there has been a breakdown in the area of science education; therefore there is a great need for curriculum reform so that the vision and mission will be clearly stated and that the stakeholders will be fair when redesigning the curriculum so that it satisfies the needs of students. There have been recommendations for education programs emphasized issues, such as updated scientific and technologic knowledge, application of contemporary learning theory and teaching strategies” (Bybee & McInerne, 1995). Also, there is a consensus amongst science teachers that students’ study too many areas, without enough depth in each, therefore, a reform of the curriculum is of great need. Rodger W. Bybee of The National Academy of Science also reveals that the level of support for curriculum reform is unprecedented in the history of American education. Additionally, the curricula in middle schools contain too many disconnected themes. In addition, each topic is given equal priority which discourages the in-depth study of foundational topics. It is therefore recommended a revised curriculum that emphasizes a more practical set of foundational themes and concepts are needed in the study of science. For this study, the researcher used a combination of methods to gather data that was then analyzed. Questionnaires, surveys and observation were the channels to acquire information. The purpose of the study is to examine if education and curriculum reform can impact the way we learn, and how. The analyzed data will be used for further research as well as to influence curriculum reform in educational systems.